2020
DOI: 10.1038/s41598-020-72751-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of regeneration and Agrobacterium-mediated transformation of Stevia (Stevia rebaudiana Bertoni): a commercially important natural sweetener plant

Abstract: Stevia rebaudiana Bertoni is a commercially important zero calorie natural-sweetener herb which produce sweet compounds known as steviol glycosides. Rising demands of steviol glycosides by food and beverage industries has led to an increase in its cultivation in various countries. Unfortunately, stevia cultivation faces 2–25% yield penalty due to weeds which further adds to its cultivation cost. To resolve this major challenge, Agrobacterium-mediated genetic transformation of in vitro derived stevia-nodal expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We showed that seedling incubation in the dark, both pre‐ and post‐infiltration, were critical for successful transformation, increasing transformation rates by five‐ to 13‐fold. Most Agrobacterium ‐infiltration methods do not include a pre‐infiltration dark incubation (Acanda et al, 2021 ; Cao et al, 2017 ; Lu et al, 2017 ; Salazar‐González et al, 2023 ; Sparkes et al, 2006 ; Taak et al, 2020 ; Zhang et al, 2020 ). Our previous Agro infiltration method included a pre‐infiltration dark incubation based on the Lee and Yang protocol (Lee & Yang, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that seedling incubation in the dark, both pre‐ and post‐infiltration, were critical for successful transformation, increasing transformation rates by five‐ to 13‐fold. Most Agrobacterium ‐infiltration methods do not include a pre‐infiltration dark incubation (Acanda et al, 2021 ; Cao et al, 2017 ; Lu et al, 2017 ; Salazar‐González et al, 2023 ; Sparkes et al, 2006 ; Taak et al, 2020 ; Zhang et al, 2020 ). Our previous Agro infiltration method included a pre‐infiltration dark incubation based on the Lee and Yang protocol (Lee & Yang, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, we are the first to experimentally show that an overnight pre-infiltration dark incubation of seedlings significantly enhanced transformation efficiency by seven-to 13-fold. In contrast to pre-infiltration dark incubation, post-infiltration dark incubations followed by light treatment are common but not standardized in Agroinfiltration protocols (Lee & Yang, 2006;Salazar-González et al, 2023;Taak et al, 2020;Zhang et al, 2020); many protocols contain post-infiltration light treatments (Acanda et al, 2021;Cao al., 2017;Lu et al, 2017). The dark encourages Agrobacterium growth (Oberpichler et al, 2008)…”
Section: Pre-and Post-infiltration Dark Incubationmentioning
confidence: 99%
“…At present, the BAR gene was isolated from Streptomyces hygroscopicus in existing transgenic crops resistant to phosphine glufosinate, and it was transferred into the crops to make them resistant to phosphine glufosinate. At present, researchers have studied different crops with BAR gene transfer [30,[57][58][59][60]. BAR gene not only can improve resistance to the herbicide glufosinate but also play a role in the salt stress and flowering of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that cotyledonary node was the most appropriate explant for regeneration 21 23 and it performed best for in vitro regeneration or Agrobacterium -mediated transformation in several plant species such as Lupinus albus 24 , Passiflora caerulea L . 25 , Cicer arietinum L. 26 , Lallemantia iberica 6 , Glycine max 27 and Stevia rebaudiana Bertoni 28 .…”
Section: Discussionmentioning
confidence: 99%